Case Report: A wolf in another wolf's clothing: point-of-care ultrasound in a patient with an acute exacerbation of chronic obstructive pulmonary disease - Jordan K. Leitch; Nicole A. Rocca (CINQUILL Medical Publishers Inc., 2017)
Patients often present to hospital, and to the Intensive Care Unit (ICU) in particular, in situations that render them unable to provide an accurate (or any) clinical history to facilitate diagnosis. These patients also typically have multiple, serious medical co-morbidities, which further makes diagnosing and initiating an appropriate treatment difficult. Furthermore, the investigations performed to optimally diagnose acute critical medical conditions are often only possible in remote locations in the hospital or only available during regular daytime work hours, both of which are a concern with critically ill patients.